Ultrasmall theranostic nanozymes to modulate tumor hypoxia for augmenting photodynamic therapy and radiotherapy. (18th December 2019) - Dan, Qing; Hu, Dehong; Ge, Yongshuai; Zhang, Shiyu; Li, Sanqing; Gao, Duyang; Luo, Wanxian; Ma, Teng; Liu, Xin; Zheng, Hairong; Li, Yingjia; Sheng, Zonghai
Abstract : A theranostic nanozyme (Au NCs-ICG) decomposes intratumoral H2 O2 to O2, subsequently enhancing photodynamic therapy and radiotherapy with the guidance of multimodal imaging. Abstract : Photodynamic therapy (PDT) and radiotherapy (RT) are oxygen-dependent treatment strategies for solid tumors in clinics. However, the hypoxic tumor microenvironment induced by uncontrolled cancer cell proliferation significantly reduces the therapeutic efficacy of these strategies. Here, we rationally constructed indocyanine green (ICG)-loaded ultrasmall gold nanoclusters (Au NCs-ICG) as theranostic nanozymes for modulating tumor hypoxia and augmenting cancer PDT and RT, respectively. The constructed Au NC-ICG nanozymes with an ultrasmall particle size (∼1 nm) exhibited favorable renal clearance performance, high substrate affinity ( K m ≈ 2 mM) and good catalase-like activity ( V max ≈ 4.55 × 10 −3 mM s −1 ). In 4T1 tumor-bearing mouse models, high tumor accumulation of Au NC-ICG nanozymes was clearly visualized by near-infrared fluorescence, photoacoustic and computed tomography imaging, showing the potential for the monitoring and guidance of PDT and RT. In addition, the Au NCs-ICG nanozymes effectively decomposed intratumoral H2 O2 into O2 for overcoming hypoxia and subsequently enhancing PDT and RT, respectively. Moreover, the inherent X-ray absorption capacity of Au NCs-ICG greatly deposited radiation energy within the tumor region and further improved cancer RT. The integration of multimodal imaging, tumor hypoxia regulation, and effective therapy into ultrasmall Au NCs-ICG nanozymes shows great potential for cancer theranostic applications.